(3GdSYGOI GdaGNQI aj SjGOI GdBNQIs - (3dWa Gddg (B" (3dWaj (B" (3Hf MSf GdJhbGJj GdQhej GdMfaj,J (B904 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg GdSYGOI GdaGNQI ai SjGOI GdBNQI s
(3BNQgG (B:s
(3gPg GdYdhe GdKdGKI jfJaY ajgG HGdGWdGY Ydi GdSjQ GdaGVdIQMe Gddg JYGdi def OYG dcGJHg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B242 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B154s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B15s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs